Ghrelin Plasma Levels After 1 Year of Ketogenic Diet in Children With Refractory Epilepsy - Marchiò, Maddalena; Roli, Laura; Lucchi, Chiara; Costa, Anna Maria; Borghi, Matteo; Iughetti, Lorenzo; Trenti, Tommaso; Guerra, Azzurra; Biagini, Giuseppe (Frontiers in Nutrition, 2019)
The ketogenic diet (KD) is a high-fat, low carbohydrate nutritional treatment adopted in several countries for refractory epilepsy. However, the use of KD is limited by adverse events including growth retardation. In a previous investigation, we demonstrated that ghrelin is reduced in children maintained on KD for 3 months. As ghrelin regulates growth hormone (GH) secretion, it can be hypothesized that growth retardation depends on the reduced ghrelin availability. To assess this hypothesis, in this study we evaluate ghrelin and growth during 1 year of KD. We examined a small cohort of 6 children (2 males and 4 females, age range 3 – 10.4 years) affected by refractory epilepsy, who received the KD as add-on treatment. All patients were on drug polytherapy. Endpoints of the study were: (i) ghrelin plasma levels at 0, 15, 30, 90, and 365 days from KD onset, (ii) growth, and (iii) seizure control by ketogenesis. Ghrelin levels were -53% and -47% of basal levels, respectively, at 90 and 365 days (P < 0.05 for both). Mean height index z scores were reduced, but not significantly, by comparing basal values with those at the end of observation. Instead, body mass index z scores slightly increased. Ketosis induced by the KD was within 2-5 mmol/L and satisfactorily reduced the seizure frequency (>50%) in all patients. We show that ghrelin plasma levels are consistently reduced in children with refractory epilepsy and maintained on the KD. This change was associated with low growth indexes in the majority of patients.